Biodegradation of oily wastewater by pure culture of bacillus cereus - Marina Bujang; Noor Azlina Ibrahim; Aweng Eh Rak (2013)
The discharges of oily wastewater to environment caused serious damages to human, animal and environment and bioremediation are an attractive alternative to chemical method for removal of hydrocarbon from industrial effluents. This study has demonstrated a very good biodegradation capability of oily wastewater by Bacillus cereus. In spite of the complex composition of oily wastewater from three different automotive workshops, biodegradation could be accomplished by Bacillus cereus. The total hydrocarbon in oily wastewater degraded by the Bacillus cereus expressed in percentages showed that the Bacillus cereus has the ability to degraded oily wastewater component in range 3% to 91%. From three different oily wastewater samples from different automotive workshop in Kota Bharu, the highest growth and degradability was obtained on oily wastewater from automotive workshop T. After 5 days of incubation, from 5% to 91% of oily wastewater components from automotive workshop T were removed by Bacillus cereus. Meanwhile, Bacillus cereus degraded only 20% to 62% of hydrocarbon components present in oily wastewater collected from automotive workshop P and 3% to 47% of hydrocarbon component in oily wastewater from automotive workshop K. The present studies suggested that the Bacillus cereus grew maximally on the three different oily wastewaters from automotive workshops when supplied as the sole source of carbon and energy and the greatest Bacillus cereus growth was detected on oily wastewater from automotive workshop T followed by oily wastewater from automotive workshop K and automotive workshop P. Apart from growth, the changes in pH in MSM medium during oily wastewater degradation by Bacillus cereus were also determined and it found that the pH of medium during the degradation of oily wastewater by Bacillus cereus was at acidic condition for all flasks. In conclusion, this study demonstrated the hydrocarbon degrading organism can be isolated from hydrocarbon polluted area and the degrading ability by Bacillus cereus is a clear indicator that this bacteria can be applied in the bioremediation techniques.